Minoritized women reading race and ethnicity: intersectional approaches to constructed identity and early Christian texts - Smith, Mitzi J.; Choi, Jin Young (Feminist studies and sacred texts, 2020)
"This book consists of cutting-edge analyses of constructions of racial/ethnic identities in early Christian texts and contemporary contexts from the perspectives of minoritized nonwhite women New Testament scholars. The range of intersectionality comprises gender/sexuality, class, patriarchy, slavery, religion, and empire"--